Shoulder kinematics and mobility adaptations in water-polo players - Turgut, E.; Yildiz, T. I.; Demirci, S.; Eraslan, L.; Ulusoy, B.; Tok, D.; Harput, G.; Kara, D.; Duzgun, I.; Tunay, V. B.; Ergun, N. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: There is limited research to demonstrate how scapular kinematics and shoulder-related physical characteristics are affected in water-polo players, who undertake swimming and repetitive throwing activity. The aim of this study was to investigate possible adaptations in the three-dimensional scapular kinematics and in glenohumeral internal rotation, external rotation range of motion and shoulder posterior-capsule tightness in water-polo players. METHODS: Fourteen water-polo players and 14 asymptomatic volunteers participated in the study. The scapular kinematics were recorded using an electromagnetic tracking device during the scapular plane shoulder elevation. Additionally, shoulder range of motion and posterior-capsule tightness were evaluated. Analysis of variance models were used to make comparisons between groups. RESULTS: Although there was a trend toward increased scapular internal rotation and downward rotation in the throwing shoulders of water-polo players, comparisons revealed there was no significant differences in kinematics, shoulder internal-external range of motion and posterior-capsule tightness between the throwing shoulders of the players and dominant shoulders of the control participants. CONCLUSIONS: The throwing shoulders of water-polo players did not demonstrate alterations in shoulder kinematics and mobility parameters.